Mode Choice of Undergraduates : A Case Study of Lecture Trips in Nigeria. - Moses Olaniran Olawole; Olabisi Michael Olapoju (Indonesian Journal of Geography, 2016)
Abstract Travel behavior and determinants of mode choice of university students in Nigeria are neither well understood nor well represented in literature. This study model is modal choice of undergraduates, using data from students travel survey and logistic regression to determine factors influence modal choice of undergraduate students in Obafemi Awolowo University Ile-Ife, Nigeria. The results indicate that walking dominate modes for on-campus and commercial bus for off-campus students, while motorcycles taxi is used by few of the sample. Mode choices are influenced by a combination of socio-economic and trip factors. A key finding is extent that these variables positively affect the odds of using walk and commercial bus modes especially with reference to student residence: on and off-campus.  The results suggest investment in pedestrian infrastructure and development of intermodal transport system as a means of making the university livable and attractive.Abstrak Kebiaasaan perjalanan dan penentu moda dari mahasiswa di Nigeria tidak juga dipahami dengan baik atau dijelaskan dalam literatur. Model penelitian ini adalah pemilihan moda mahasiswa menggunakan data dari survei perjalanan mahasiswa dan regresi logistik untuk menentukan faktor penyebab pilihan moda dari mahasiswa di Universitas Obafemi Awolowo, Ile-Ife, Nigeria. Hasilnya menunjukkan berjalan mendominasi pilihan untuk ke kampus dan kendaraan bus umum untuk mahasiswa di luar kampus, sementara sepeda motor taksi digunakan oleh beberapa sample. Pilihan cara dipengaruhi oleh kombinasi dari sosial-ekonomi dan faktor kunjungan. Inti penelitian adalah luasnya variabel positif mempengaruhi peluang dari berjalan dan kendaraan bus umum terutama rujukan ke asrama mahasiswa, dalam maupun luar kampus. Hasil penelitian menyarankan investasi pada infrastruktur pejalan kaki dan pengembangan dari sistem transportasi antarmoda sebagai sarana membuat universitas layak huni dan menarik.